Equatorial Guinea versus the Cameroon-Gabon pair in Central Africa (1960-2012): The History of a Small State in Search of Emancipation and Power - (:unkn) unknown (My University, 2018)
This thesis dissertation whose topic is " La Guinée Équatoriale face au couple Cameroun-Gabon en Afrique Centrale (1960-2012) : Histoire d’un petit État en quête d’émancipation et de puissance ”, aims at tracing the history of relations between the Cameroon-Gabon pair and Equatorial Guinea in the process of regional integration in Central Africa, emphasizing the quest of power by Equatorial Guinea in the sub-region. It also aims at answering the main question: How do the attitude and acts of Equatorial Guinea in Central Africa explain the quest for emancipation and power vis-à-vis the Cameroon-Gabon pair? This thesis uses an interdisciplinary approach based on qualitative and content Analysis from various sources.From 1960 to 1979, relations between Equatorial Guinea and Cameroon-Gabon pair fluctuated between cooperation, aid and conflict. Following a coup overthrowing Macías Nguema, Obiang Nguema Mbasogo soothed relations with his two francophone neighbors, which led to the accession of his country to the UDEAC. Being very poor, Equatorial Guinea had no position of senior responsibility; any community institution had its headquarter in Equatorial Guinea and the country did not claimed it. In 1990, the discovery and exploitation of oil in Equatorial Guinea changed the face of this country in the sub-region and enabled him to claim and have the institutional reform of CEMAC. This institutional reform enabled Equatorial Guinea to gain senior leadership positions within the CEMAC to the dismay of the Cameroon-Gabon pair. The thesis concludes that despite all the maneuvers of Equatorial Guinea in the CEMAC zone about leadership; it does not have all the criteria enabling it to become the leading power in the sub-region.
Keywords: African Research